MEMFASILITASI KEMAMPUAN REFLEKSI DIRI MAHASISWA KEDOKTERAN: APA DAN BAGAIMANA? - Dwita Oktaria; Dian Puspita Sari; Diantha Soemantri; Nadia Greviana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Self-reflection skill is essential for doctors to develop professional attitudes, therapeutic relationships between doctor-patient, and lifelong learning. Self-reflection needs to be developed during medical study in a structured and systematic manner, either in a professionalism course or other learning opportunities. Gaps: Reflective learning in medical education often only focuses on improving the understanding of professionalism rather than developing students' self-reflection skills. In addition, the opportunity to conduct self-reflection in the curriculum is still limited, and assessment of reflection ability is challenging. There are doubts as to whether self-reflection needs to be assessed. Recommendation: The opportunity to conduct guided self-reflection needs to be allocated in a structured manner in the curriculum to develop learners’ reflection skills. The strategy to develop self-reflection skills involves a series of educational interventions, including providing guidance and feedback on reflection and ensuring that students' self-reflection is assessed. Reflections on feedback obtained within the learning process can help students to take advantage of the feedback provided, develop self-assessment skills, and improve their performance. In assessing reflection, educators need to consider the time, approach, and purpose of assessment and ensure that the focus is on learners’ ability to self-reflect. Self-reflection needs to be cultivated by creating a conducive environment. The process of mentoring and providing constructive feedback is essential in building reflective dialogue with students to increase students’ motivation to reflect.